Las redes sociales y su influencia en los adolecentes - Jácome Yanéz, Paola Marina (2017)
The research project aims to understand how adolescents use social networks, in this case Facebook to interact with known or unknown people as well as to identify how this affects the privacy and security of information. The project seeks to how the use of social networks influences the privacy and security of information of adolescents of Victoria Vascones Cuví secondary school of eleven graders students in the city of Latacunga. The networks have modified the diverse activities and communication manifestations of young people in Ecuador, as well as around the world. The internet is created to facilitate social relations and access to information in an agile and collective way. Despite the advantages that can be gained by the use of new technologies, especially web 2.0 platforms, they are not exempt from dangers that mainly affect the privacy and security of users. To obtain real data to justify the project, the qualitative and quantitative methodology has been applied. For this purpose, different techniques have been used based on the application of an observation form, a questionnaire and interviews with the adolescents from the eleven graders of Victoria Vasconez Cuvi secondary school and a specialists in the subject; with the application, it was obtained criteria on how teenagers use Facebook in order to be connected with known people, family and friends. At the same time they express anger, feelings, emotions; something similar happens with the publications of the networks that usually frequent, without taking into consideration security and privacy when publishing the data on Facebook. This research project aims to significantly favor adolescents, parents and institution; because through the information collected, it can be understood that adolescents by using social networks have become databases that collect personal information and documents on daily life activities. Also exposing information to other people that time ago teenagers avoided share the information easily.